Two new species of the little-known Genus Bacescuella Hrabĕ (Oligochaeta, Tubificidae) from the North Atlantic - Erséus, C. (Zoologica Scripta, 1978)
Bacescuella arctica sp.n. and B. parvithecata sp.n. are described, from northern Scandinavia and Bermuda respectively. The de?nition of Bacescuella Hrabe, 1973, which belongs to the subfamily Phallodrilinae, is modi?ed; and the morphology of the new species and B. pontica Hrabe, 1973, is discussed. All species possess uniform tubular male ducts ending in large penes. Prostate glands are present at ental ends of atria as well as at bases of penes. Vas deferens is absent in B. pontica, very short in B. parvithecata. The reproduction of Bacescuella involves external spermatophores.